The gastrointestinal microbiota in the development of ME/CFS: a critical view and potential perspectives - Stallmach, Andreas; Quickert, Stefanie; Puta, Christian; Reuken, Philipp A. (Frontiers in Immunology, 2024)
Like other infections, a SARS-CoV-2 infection can also trigger Post-Acute Infection Syndromes (PAIS), which often progress into myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS). ME/CFS, characterized by post-exercise malaise (PEM), is a severe multisystemic disease for which specific diagnostic markers or therapeutic concepts have not been established. Despite numerous indications of post-infectious neurological, immunological, endocrinal, and metabolic deviations, the exact causes and pathophysiology remain unclear. To date, there is a paucity of data, that changes in the composition and function of the gastrointestinal microbiota have emerged as a potential influencing variable associated with immunological and inflammatory pathways, shifts in ME/CFS. It is postulated that this dysbiosis may lead to intestinal barrier dysfunction, translocation of microbial components with increased oxidative stress, and the development or progression of ME/CFS. In this review, we detailed discuss the findings regarding alterations in the gastrointestinal microbiota and its microbial mediators in ME/CFS. When viewed critically, there is currently no evidence indicating causality between changes in the microbiota and the development of ME/CFS. Most studies describe associations within poorly defined patient populations, often combining various clinical presentations, such as irritable bowel syndrome and fatigue associated with ME/CFS. Nevertheless, drawing on analogies with other gastrointestinal diseases, there is potential to develop strategies aimed at modulating the gut microbiota and/or its metabolites as potential treatments for ME/CFS and other PAIS. These strategies should be further investigated in clinical trials.